Be a specialist - Rokes, John Albert (My University, 1893)
Introduction: “The life is measured by the soul’s advance, the enlargement of its powers, the expanded field wherein it ranges, till it burns and glows with heavenly joy, with high and lasting hope.” The objects of a true education are to prepare one for greater enjoyment of this life, to give him greater influence over his fellow-men, and place him in the way of doing, with the same exertion, more and better work, whether physical or mental.
Citation: Rokes, John Albert. Be a specialist. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Education; Life; Influence; Theses; Manuscripts (documents)